PENGGUNAAN KECERDASAN BUATAN (AI) DALAM PENDIDIKAN: MANFAAT DAN RISIKO - Rima Dewi Setiani I; Rutin Winarsih; Ari Abi Aufa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to analyze the use of artificial intelligence (AI) in education, covering its benefits and risks. This study discusses the basic concepts of AI, how it works, and its impact on the teaching and learning process. The method used is qualitative research through a literature study that collects data from books, journals, and relevant research. The results show that AI can improve the personalization of student learning, teacher work efficiency, and expand access to education, but it still poses risks such as data privacy, technological dependence, and reduced human interaction. This study also found that the application of AI requires ethical regulations, digital literacy, data security, and cross-sector collaboration. In conclusion, AI has the potential to be a strategic partner in improving the quality of education, as long as it is used wisely and in balance with human values.